Learner Autonomy of Engineering Students: Validating the PRO-SDLS scale in a Portuguese context - Duarte, Marina (International Journal of Engineering Pedagogy (iJEP), 2014)
In the European Higher Education Area, lifelong learning has been recognized as an essential element, being critically important given the rapid pace of change of society, namely in engineering and technology. Learner autonomy and self-direction in learning in higher education has become increasingly important as a way to promote lifelong learning and the ability to continuously learn. This study is a first step in the adaptation and validation of a Portuguese version of the Personal Responsibility Orientation to Self-Direction in Learning Scale (PRO-SDLS) to undergraduate engineering students. Using factor and reliability analysis, 12 items of the translated scale showed strong validity and reliability. The findings indicate that the PRO-SDLS can be used with engineering undergraduate students, but there are some differences between the original learner autonomy construct and the one that emerges from this adaptation. More data collection is suggested. The possibility of interviews and focus groups is also mentioned.